First observation of Bs -> J/psi f0(980) decays - Collaboration, TL; Aaij, R; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Cartelle, P; Jr, A; et al. (2011)
Using data collected with the LHCb detector in proton-proton collisions at a centre-of-mass energy of 7 TeV, the hadronic decay Bs -> J/psi f0(980) is observed. This CP eigenstate mode could be used to measure mixing-induced CP violation in the B_s system. Using a fit to the pi+ pi- mass spectrum with interfering resonances gives R_{f0/phi} = [Gamma(Bs -> J/psi f0, f0 -> pi+ pi-)]/[Gamma(Bs -> J/psi phi, phi -> K+K-)] = 0.252^{+0.046+0.027}_{-0.032-0.033}, where the uncertainties are statistical and systematic, respectively.